Computational Study of Cu–Containing Artificial DNA: Twist Angle Dependence of Magnetism. Issue 17 (25th October 2016) - Orimoto, Yuuichi; Aoki, Yuriko
Abstract: The magnetic properties of a copper‐containing artificial DNA (a 2, 6‐dipicolinate−Cu(II)−pyridine complex‐based artificial DNA) were theoretically investigated at the ab initio molecular orbital (MO) theory level from the standpoint of the relationship between the twist angle about the DNA chain axis and its high‐spin (HS) stability. It was found that HS stability gradually increased with increasing twist angle at the Hartree‐Fock level. Consideration of the electron correlation effects using a perturbation theory emphasized on the twist angle dependence of HS stability (leading to an increase in the magnetic contrast for the twist angle). Detailed analyses based on MOs revealed that the trend in HS stability is related to the twist angle dependence of the delocalization of singly occupied MOs for the highest spin state and that of the highest doubly occupied MO for the lowest spin state. Abstract : Twist angle dependence of magnetic property: The magnetic properties of a Cu‐containing artificial DNA model (see picture) were theoretically investigated at the ab initio molecular orbital (MO) theory level in terms of the relationship between the twist angle about the DNA chain axis, its high‐spin stability, and the shape of MOs.